2016
DOI: 10.1016/j.jconrel.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular sustained release of atorvastatin from a hydrogel-microparticle delivery system decreases intimal hyperplasia

Abstract: tissues, except at a very low concentration (0.044 ng/mg) in the liver, suggesting a very low risk 50 of systemic toxicity of locally delivered ATV. Additionally, the ex vivo data showed that ATV in 51 solution permeates through isolated human saphenous veins and thus is a good candidate for 52 perivascular delivery. 53Our data demonstrate that a local biphasic ATV release on the mice ligated carotid 54 efficiently prevents the development of IH without apparent toxicity. 55 56

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…Delie and coworkers developed an easily applicable drug delivery system for the prevention of intimal hyperplasia, through a single administration of a cross‐linked hyaluronic acid hydrogel/poly‐lactic‐co‐glycolic acid (PLGA) microparticle formulation loaded with atorvastatin. Theirs in vivo studies showed that the combination of a fast and sustained release of atorvastatin provided a synergistic effect, which efficiently inhibited the development of intimal hyperplasia . Ma and coworkers synthesized injectable composite hydrogels composed of alginate microspheres and PLGA–PEG–PLGA hydrogel as a double barrier system to greatly suppress the burst release and to prolong the release time of water‐soluble drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Delie and coworkers developed an easily applicable drug delivery system for the prevention of intimal hyperplasia, through a single administration of a cross‐linked hyaluronic acid hydrogel/poly‐lactic‐co‐glycolic acid (PLGA) microparticle formulation loaded with atorvastatin. Theirs in vivo studies showed that the combination of a fast and sustained release of atorvastatin provided a synergistic effect, which efficiently inhibited the development of intimal hyperplasia . Ma and coworkers synthesized injectable composite hydrogels composed of alginate microspheres and PLGA–PEG–PLGA hydrogel as a double barrier system to greatly suppress the burst release and to prolong the release time of water‐soluble drugs .…”
Section: Introductionmentioning
confidence: 99%
“…This formulation was shown to reduce IH by 68% at 4 weeks in a mouse carotid artery ligation model. 13 …”
Section: Discussionmentioning
confidence: 99%
“…This paradigm for prolonging drug efficacy was further supported by a recent report in which combining PLGA microparticles (15 μ m in diameter) with a cross-linked hyaluronic acid gel markedly extended drug release and inhibition of IH in a mouse model for 4 weeks. 13 These studies indicate that prolonged drug release produces durable efficacy. Thus, a perivascular delivery system capable of long-term drug release is highly desirable for developing effective treatments for IH.…”
Section: Introductionmentioning
confidence: 96%
“…These systems should have adequate mechanical properties in order to be bent, sutured or injected and to remain on site for the desired period of time. Semi-solids, most frequently gels, present the advantages of easy handling and conformable covering of the graft [66]. Indeed, a gel should be easily manipulated by the surgeon to cover the anastomosis as well as the graft itself ( Fig.…”
Section: Properties Of Perivascular Systemsmentioning
confidence: 99%